Reaction kinetics and solubility in water‐organic binary solutions are governed by similar solvation equilibria. (19th October 2015) - Salmar, Siim; Vaalma, Morten; Vider, Henry; Tenno, Tiina; Kuznetsov, Aleksei; Järv, Jaak; Tuulmets, Ants
Abstract : The solvation effects observed in water‐organic solutions were studied by combining data for reaction kinetics and dissolution equilibria by means of a linear free‐energy (similarity) analysis. Kinetic data for the pH‐independenthydrolysis of (4‐methoxyphenyl)‐2, 2‐dichloroacetate measured in this work and solubility data for naphthalene, and other substrates of low polarity, in aqueous binary mixtures of methanol, ethanol, acetonitrile, dimethyl sulfoxide (DMSO), and 1, 4‐dioxane were used. Linear similarity relationships were discovered for these data over the full range of solvent compositions studied. To gain insight into the similarities observed between these different phenomena, molecular dynamics simulations were carried out for naphthalene and an ester in water–acetonitrile solutions. The results revealed considerable preferential solvation of these substrates by the co‐solvent. Linear relationships between the experimental data and the mole fractions of acetonitrile in the solvation shells of substrates were found. Surprisingly, a linear relationship was found between the mole fractions of acetonitrile in the solvation shells of the ester and naphthalene. This linearity indicated that a similar solvation mechanism governs even such different phenomena as dissolution and reaction kinetics. The relationships between the experimental data and the results of the molecular dynamics calculations found in this work explained the solvent effect observed in water‐organic solutions on the molecular level. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Linear relationships between reaction kinetics and dissolution equilibria in water‐organic mixtures were found to be valid over the full range of solvent compositions. The molecular dynamic simulations of solvation in water–acetonitrile solutions indicated considerable preferential solvation of solutes. Comparing experimental data with results of the molecular dynamic calculations revealed that the solvent effects are determined by similar solvation equilibria.